As espécies de Paspalum L. (Poaceae) dos grupos Virgata e Quadrifaria no Brasil - Distribuição e ecologia - Gomes, Maria Judith Ismael Richi [UNESP]; Monteiro, Reinaldo [UNESP] (My University, 1996)
The Brazilian species of Paspalum L. (Poaceae) groups Virgata and Quadrifaria are revised based on herbarium material and live specimens of recent collections. The Virgata taxa are P. wettsteinii, P. rufum, P. regnellii, P. conspersum, P. virgatum and P. commune, while Quadrifaria encompasses P. intermedium, P. densum, P. millegrana, P. durifolium, P. brunneum, P. usteri, P. plenum, P. quadrifarium, P. coryphaeum, P. exaltatum and P. haummanii. Both groups are commonly found throughout the country, but rare in the wet areas of the Amazonian forest, and better characterized as megatherm plants.
The species of Paspalum L. (Poaceae), groups Virgata and Quadrifaria. in Brazil - Distribution and ecology
Keywords: Grass; Grass distribution; Grass ecology; Paspalum